2022
DOI: 10.1002/ppap.202200051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a thin organosilicon layer prepared by atmospheric pressure plasma on wood flame retardancy

Abstract: In a high-rise building, due to the risk of flame spread and strict regulations associated, wood use is limited for interior finishes. This study aimed to evaluate the effect of a thin organosilicon layer (∼500 nm) prepared by atmospheric pressure plasma on the fire behavior of a wood substrate. The coating was deposited from hexamethyldisiloxane in argon on both untreated wood and wood with a preparatory coating of primer. The primer reduces the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…However, its intrinsic high flammability brings about fire hazards which tends to cause huge economic losses and casualties 6 9 . Various methods have been developed to improve fire safety of wood, among which, flame-retardant coating is the most striking strategy as it could be easily applicable on wood 10 13 . For example, Pedro et al proposed a fireproof coating based on lignin, tannins and inorganic nanoparticles, which significantly reduced the linear combustion speed by 50% compared with pure wood 14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, its intrinsic high flammability brings about fire hazards which tends to cause huge economic losses and casualties 6 9 . Various methods have been developed to improve fire safety of wood, among which, flame-retardant coating is the most striking strategy as it could be easily applicable on wood 10 13 . For example, Pedro et al proposed a fireproof coating based on lignin, tannins and inorganic nanoparticles, which significantly reduced the linear combustion speed by 50% compared with pure wood 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, primer polymer films have been used in wood-related applications [11][12][13]. For example, a study on flame-retardant wood revealed that only the synergistic effect between the primer and the plasma layer could lead to flame retardancy, and the primer helped to smooth the surface of the plasma coating, seal the pores of the wood, and promote the formation of a more uniform plasma layer [11]. In wood 3D printing, primer can achieve a high bonding strength [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, its intrinsic high ammability brings about re hazards which tends to cause huge economic losses and casualties [6][7][8][9]. Various methods have been developed to improve re safety of wood, among which, ame-retardant coating is the most striking strategy as it could be easily applicable on wood [10][11][12][13]. For example, Pedro et al proposed a reproof coating based on lignin, tannins and inorganic nanoparticles, which signi cantly reduced the linear combustion speed by 50% compared with pure wood [14].…”
Section: Introductionmentioning
confidence: 99%